Road User Charges : Current Practice and Perspectives in Central and Eastern Europe - Queiroz, Cesar; Rdzanowska, Barbara; Garbarczyk, Robert; Audige, Michel (2014)
This paper covers the most commonly used means to charge road users, including fuel taxes, vehicle taxes, vignettes and tolls. It presents a brief survey of road user charging systems in selected European countries and a more detailed overview of current status and perspectives of road user charges in Poland. Consideration is also given to private financing of roads through different forms of public-private partnerships (PPP), including a review of potential applications of the World Bank toolkit for PPP in highways as an instrument to help decision makers and practitioners to define the best PPP approach for a specific country.